Authority and solidarity on the Estonian COVID-19 signs: In line with the government's guidelines, we ask you to wear a mask - Tragel, Ilona; Pikksaar, Aimi (Frontiers in Artificial Intelligence, 2023)
This article presents the results of a quantitative analysis of 900 Estonian COVID-19 door signs, which were studied to investigate the linguistic means of establishing and maintaining contact between the sign’s author (institution) and the addressee (client). Malinowski’s notion of ‘phatic communion’ and Laver’s notions of ‘self-oriented’ and ‘other-oriented’ utterances as means for expressing status relations – authority and solidarity – between the participants of the communication act were used to establish four types of grammatical person usage on the COVID-19 signs: (1) ‘neither 1st nor 2nd person’; (2) ‘1st person only’; (3) ‘2nd person only’, and (4) ‘both 1st and 2nd person’. Grammatical person of personal pronouns and verb forms were included. The presence and absence of two other means for expressing authority – the imperative mood and lexical expressions of authority – were analyzed within these four types of grammatical person usage. The most important difference emerged between the signs belonging to the types ‘2nd person only’ (i.e., signs with only other-oriented 2nd person, without 1st person) and ‘both 1st and 2nd person’ (i.e., signs with both self-oriented 1st person and other-oriented 2nd person). On the signs belonging to the type ‘2nd person only’ that, relying on Laver, express the higher status of the sender of the message in relation to the receiver of the message, the authors of the signs use significantly more imperative mood and less refer to an authority outside the communication act, thus putting themselves in the role of authority. However, on the signs belonging to the type ‘both 1st and 2nd person’ that, relying on Laver, express the solidarity of the sender of the message with the addressee, the authors of the signs seem less inclined to assume the role of authority (using less imperative mood) and rather call the reader of the sign to submit to some higher authority (using lexical expressions of authority, e.g., Vabariigi Valitsus ‘Government of the Republic’, Terviseamet ‘Health Board’, etc.) to which the author of the sign and the addressee are both in a subordinate position and, therefore, of equal status.